Triumph at Imphal-Kohima : How the Indian Army Finally Stopped the Japanese Juggernaut - Callahan, Raymond (Book collections on Project MUSE., 2017)
In the Spring of 1944, on the eastern frontier of India, the hitherto victorious Imperial Japanese Army suffered the worst defeat in its history at the hands of the ""British"" Fourteenth Army, most of whose units were, in fact, drawn from the Indian Army.